Comprehensive analysis of the role of diverse programmed cell death patterns in sepsis - Yu, Xiaotongning; Zhou, Zihao; Ma, Jing; Wang, Xiaonan; Zhao, Chunyu; Hou, Anqi; Sun, Shuo (Frontiers in Immunology, 2025)
BackgroundSepsis, a life-threatening condition with persistently high mortality, involves dysregulated immune responses and programmed cell death (PCD). However, the specific roles and interactions of diverse PCD pathways in sepsis pathogenesis remain incompletely understood. This study aimed to systematically characterize PCD patterns and their clinical relevance in sepsis.MethodsWe integrated three bulk transcriptomic datasets (81 controls, 165 sepsis patients) and one single-cell RNA sequencing (scRNA-seq) dataset (4 controls, 4 early sepsis patients, 52,315 cells) from public databases. Gene set variation analysis (GSVA) quantified activity of 13 PCD pathways. Immune infiltration was assessed via single-sample gene set enrichment analysis (ssGSEA). A cell death-associated signature (CDS) risk score was developed using least absolute shrinkage and selection operator (LASSO) regression. scRNA-seq analysis identified cell-type-specific PCD activation and intercellular communication using Seurat, AUCell, and CellPhoneDB. Additionally, an independent RNA-seq cohort generated from our own sequencing of sepsis patients and healthy controls was used for external validation.ResultsTranscriptomic analysis identified 5,591 differentially expressed genes enriched in immune and cell death pathways. Four PCD pathways-ferroptosis, disulfidptosis, NETosis, and entotic cell death-were significantly upregulated in sepsis and strongly correlated with immune cell infiltration, such as activated dendritic cells and neutrophils. The CDS risk score, based on 18 core PCD genes, showed excellent diagnostic accuracy across both public microarray datasets (AUC = 0.961 and 0.844) and our independent high-throughput RNA-seq dataset (AUC = 0.975). scRNA-seq revealed monocytes as dominant effectors, exhibiting heightened activation of ferroptosis, entotic death, and netotic pathways alongside metabolic reprogramming, including enhanced glutathione metabolism and oxidative phosphorylation (OXPHOS). Furthermore, monocyte-centric intercellular communication was dysregulated in sepsis, featuring upregulated MIF-CXCR4, ANXA1-FPR2, and HLA-KIR signaling axes.ConclusionsBy integrating public microarray and single-cell transcriptomic data with independent high-throughput sequencing validation, this study analysis identifies ferroptosis, disulfidptosis, netotic death, and entotic death as key dysregulated PCD pathways in sepsis, with monocytes serving as central hubs integrating PCD, metabolic reprogramming, and immune communication. The CDS risk score provides a robust diagnostic and stratification tool. Targeting monocyte-driven PCD-metabolism-communication networks offers promising avenues for precision immunotherapy in sepsis.